Definition of The “Minister” in Government Regulation 11/2021 Concerning Village-Owned Enterprises - Saptono Jenar (Constitutionale)
Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises (GR VOE) is one of the implementing regulations (verordnung or delegated laws and regulations) of Law Number 11 of 2020 concerning Job Creation (Job Creation Law). However, there is a different definition regarding the word "Minister" stated under Article 1 number 17 GR VOE with that of the provisions in Article 117 number 1 of the Job Creation Law. Definition of the word "Minister" as referred to in Article 1 number 17 GR VOE is a legal issue when it is viewed from a prescriptive because it indicates a vertical inconsistency. In order to discuss these legal issues, the author uses a statutory approach and a conceptual approach. The results of the study show that definition of the word "Minister" in Article 1 number 17 GR VOE is invalid, because it is not in accordance with its parental act (Job Creation Law) and the principle of lex superiori derogat legi inferiori. Based on the results of the study, the authors suggest that definition of the word "Minister" as referred to in Article 1 number 17 GR VOE needs to be revised in line with Article 117 number 1 of the Job Creation Law.